The theory of the purposes of the law as the reflection of the dynamism of Islamic law - Laluddin, Hayatullah; Abdul Razak, Mohd. Abbas; Husni, Ahmad Muhammad (IIUM Press, International Islamic University Malaysia, 2023)
It is an undeniable fact that the textual sources of the law are limited whereas, the issues and problems that human society encounters with are unlimited. This obviously necessitates the adaptation of a dynamic method by virtue of which solutions could be sought through its application into the text of the law based on its objectives and purposes. Therefore, the theory of the purposes of law by virtue of its comprehensive nature reflecting the dynamism of the Islamic Law could be used to this end. The theory draws its structure on two fundamental elements: the underlying meanings and purposes of the text, and the general principles that are based on the consideration of maslahah.Thus it has the potential of extending the law beyond the confines of its literalimplication. In view of the dynamic nature of the theory and its significance, this article attempts to investigate the underlying motion of the theory and its development. Tracing its link in the classical works on jurisprudence, it also elaborates various aspects of the methodology of discovering the purposes of the law, their relation and classification